1992
DOI: 10.1039/jm9920200511
|View full text |Cite
|
Sign up to set email alerts
|

n-Type doping of SnO2 thin films by Sb ion implantation

Abstract: The effects of Sb implantation into textured thin films of SnO, prepared by RF sputtering have been characterised by a range of techniques including secondary ion mass spectrometry (SIMS), X-ray and ultraviolet photoelectron spectroscopies (XPS and UPS), infrared reflectance, X-ray diffraction and conductivity measurements. The depth distribution of implanted 12'Sb ions at low dose is characterised by a truncated bell-shaped distribution, with mean implantation ranges of 250 8, for 90 keV implantation and 370 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…However, when the attachment energies are considered, we find the two planes (110 and 001) are very close in energy, which is in accordance with experimental observations, where the two planes are both observed. Note that the six faces with the lowest surface energies correspond exactly to those observed by experiment. To the authors knowledge, the remainder of the surfaces have yet to be observed; thus, our calculations explain the experimental observations in terms of both thermodynamic and kinetic stability, in contrast to previous atomistic studies. , …”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, when the attachment energies are considered, we find the two planes (110 and 001) are very close in energy, which is in accordance with experimental observations, where the two planes are both observed. Note that the six faces with the lowest surface energies correspond exactly to those observed by experiment. To the authors knowledge, the remainder of the surfaces have yet to be observed; thus, our calculations explain the experimental observations in terms of both thermodynamic and kinetic stability, in contrast to previous atomistic studies. , …”
Section: Introductionsupporting
confidence: 63%
“…Note that the six faces with the lowest surface energies correspond exactly to those observed by experiment. [29][30][31][32][33][34] To the authors knowledge, the remainder of the surfaces have yet to be observed; thus, our calculations explain the experimental observations in terms of both thermodynamic and kinetic stability, in contrast to previous atomistic studies. 14,15 B. Segregation Energies.…”
Section: Introductionmentioning
confidence: 92%
“…SnO 2 is easily n-dopable [70,71], but undoped samples only gain significant carrier concentrations at elevated temperatures [33][34][35] (although Fonstad et al [72] have shown concentrations of ∼10 17 cm −3 at room temperature). A clear increase in conductivity as P O 2 is decreased can be observed when temperature T > 1000 K, indicating the presence of a relatively deep donor [34].…”
Section: Introductionmentioning
confidence: 99%
“…The shell model of Freeman and Catlow [6] was used. Experiments on thin films ( [7]) support this conclusion; the (001) texture disappears on annealing.…”
Section: Results For Stannic Oxidementioning
confidence: 84%